Trade unions and worker movements in the North American communications industries. (1st April 2008) - ,
Abstract : This paper reports on a project that examines trends in North American labour movements, and specifically in the workforce, in the converging communications, culture, and information technology sectors. Drawing on documentary evidence and interviews, the paper concentrates on two important developments: efforts to unify workers across the knowledge and communication industries, and the rise of worker movements that operate in conjunction with, but outside, the formal trade union structure. The paper begins by situating these developments within debates about labour in a ''post-industrial'', ''information'', or ''network'' society. It describes the challenges facing workers in the knowledge sector, especially rapid technological change, massive corporate consolidation, the rise of the neo-liberal state and divisions between cultural and technical workers in the knowledge sector. The paper proceeds to describe how North American workers are responding within the traditional trade union system, primarily through forms of consolidation or trade union convergence (such as the Communication Workers of America), and also through worker movements operating outside the traditional trade union system in the information technology and cultural sectors (for example WashTech and the National Writers Union). The paper concludes by addressing the significance of these developments. Do they portend a rebirth of North American labour activism or do they represent its last gasps?